Sasombaugh Desa Domo Kecamatan Kampar Kiri Kabupaten Kampar (Kajian Semiotika) - Aurelia Sulistiayu; Syafrial Syafrial; Elmustian Rahman (STKIP PGRI Jombang, 2021)
AbstractThis research is entitled Sasombaugh Desa Domo Kecamatan Kampar Kiri Kabupaten Kampar (Semiotics Study). This research is based on the background of the Domo Village Community, which is part of the Kampar Malay speech community, which until now still uses the Sasombaugh oral tradition or culture, especially in traditional wedding ceremonies. Sasombaugh was created spontaneously from the party who came, while the recipient answered with a sentence that was made immediately. The purpose of this study was to determine the icon conveyed in Sasombaugh Antau Tando, then to describe the index conveyed in Sasombaugh Antau Tando and to describe the symbols conveyed in Sasombaugh Antau Tando in Domo Village, Kampar Kiri District, Kampar Regency. The research method is descriptive qualitative. Data collection techniques using documentation and library techniques. The documentation technique is in the form of Sasombaugh Antau Tando text data and data from informants and library techniques which include theories related to the object of research. Data analysis techniques are in the form of identifying data, classifying data, describing data, and concluding data. The results of the study are the icons contained in the Sasombaugh Antau Tando text include; (i) Tando ,; (ii) Tando kocik; (iii) Tando Godang; (iv) Kombuik; (v) Sirih jo Pinang; (vi) Kain Nan Saolai Bonang; and (vii) Upi Ghak. The index contained in the Sasombaugh Antau Tando text is Baati Suko. The symbols contained in the text Sasombaugh Antau Tando (i) Kamanakan and Datuk; (ii) Bano / Gubano; (iii) Baaghak; (iv) Cano; and (v) Ninik mamak. Keyword:semiotics, sasombaugh, antau tando, icons, indexes, symbolsAbstrakPenelitian ini berjudul Sasombaugh Desa Domo Kecamatan Kampar Kiri Kabupaten Kampar (Kajian Semiotika). Penelitian ini dilatar belakangi oleh Masyarakat Desa Domo yang merupakan bagian dari masyarakat tutur Melayu Kampar, yang sampai saat ini masih menggunakan tradisi atau budaya lisan Sasombaugh terutama dalam upacara adat perkawinan. Sasombaugh tercipta secara spontan dari pihak yang datang, sementara pihak penerima menjawab dengan kalimat yang dibuat seketika. Tujuan dari penelitian ini adalah untuk mengetahui ikon yang disampaikan dalam Sasombaugh Antau Tando, kemudian untuk mendeskripsikan indeks yang disampaikan dalam Sasombaugh Antau Tando dan untuk mendeskripsikan simbol yang disampaikan dalam Sasombaugh Antau Tando di Desa Domo Kecamatan Kampar Kiri Kabupaten Kampar. Metode penelitian adalah deskriptif kualitatif. Teknik pengumpulan data menggunakan teknik dokumentasi dan perpustakaan. Teknik dokumentasi berupa data teks Sasombaugh Antau Tando serta data dari informan dan teknik perpustakaan yang mencakup teori-teori yang berhubungan dengan objek penelitian.Teknik analisis data berupa mengidentifikasi data, mengklasifikasi data, mendeskripsi data, dan menyimpulkan data. Hasil penelitian adalahAdapun Ikon yang terdapat pada teks Sasombaugh Antau Tandodiataranya; (i) Tando,; (ii) Tando kocik; (iii) Tando Godang; (iv) Kombuik; (v) sirih jo Pinang; (vi) Kain Nan Saolai Bonang; dan (vii) Upi Ghak. Adapun Indeks yang terdapat pada teks Sasombaugh Antau Tando adalah Baati suko. Adapun simbol yang terdapat pada teks Sasombaugh Antau Tando (i) Kamanakan dan Datuk; (ii) Bano/Gubano; (iii) Baaghak; (iv) Cano; dan (v) Ninik mamak. Kata kunci: semiotika, sasombaugh, antau tando, ikon, indeks, simbol